Penerapan Kitab Al-‘Arabiyyah Baina Yadaik Jilid II untuk Pembelajaran Bahasa Arab Santriwati Kelas II Smp Pondok Pesantren Cahaya Qur’an Tegalwaton Tengaran Semarang T.A 2022-2023 - Zidni Fahma (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2023)
The Book Al-‘Arabiyyah Baina Yadayk as a Teaching Material in Arabic Language Learning for Female Students at Pondok Pesantren Cahaya Qur’an. Al-‘Arabiyyah Baina Yadayk is one of the teaching materials commonly used as a reference or guide for teachers and female students in Arabic language learning. This book was chosen as the teaching material for Arabic learning at Pondok Pesantren Cahaya Qur’an. This study aims to explore how the Arabic learning process in Class II (Junior High) at Pondok Pesantren Cahaya Qur’an is conducted using Al-‘Arabiyyah Baina Yadayk, to identify the learning outcomes, and to understand the supporting and inhibiting factors in using this book for learning. The research uses a qualitative approach, with data collection techniques including observation, interviews, and documentation. The data analysis technique follows the Miles and Huberman model: data reduction, data presentation, and drawing conclusions. Triangulation techniques were used by collecting multiple data sources about the implementation of Al-‘Arabiyyah Baina Yadayk in Arabic learning for female students. The results show that the application of Al-‘Arabiyyah Baina Yadayk for Arabic language learning at Pondok Pesantren Cahaya Qur’an is quite effective. This is because the book integrates the four main language skills: listening (maharah al-istima’), speaking (maharah al-kalam), reading (maharah al-qira’ah), and writing (maharah al-kitabah). There are also structured learning steps when using Al-‘Arabiyyah Baina Yadayk, which include dialogue practice, vocabulary comprehension, sentence structure understanding, listening, speaking, reading, and writing exercises. Furthermore, the study identifies supporting factors divided into two categories: internal and external. Likewise, there are inhibiting factors, also consisting of both internal and external elements.